2007
DOI: 10.1080/10810730601152755
|View full text |Cite
|
Sign up to set email alerts
|

Healthy or Unhealthy Slogans: That's the Question…

Abstract: An experiment was conducted to examine the effect on adolescents of different health appeals (healthy versus unhealthy) in ads for healthy and unhealthy perceived foods. The results did not reveal a main effect of product or slogan, but indicated a significant interaction effect between slogan and product. The healthy slogan only led to significantly more positive attitudes and purchase intentions when it promoted a healthy food product. An unhealthy food product received better results in combination with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…At first sight, the findings by Elder and Krishna [17] could suggest that multiple-sense ads can also promote healthy food. However, previous research shows that healthy food advertising and unhealthy food advertising often use different advertising techniques [33] and also call for different advertising techniques in order to be effective [34].…”
Section: Sensory Advertising For Healthy Versus Unhealthy Foodmentioning
confidence: 99%
“…At first sight, the findings by Elder and Krishna [17] could suggest that multiple-sense ads can also promote healthy food. However, previous research shows that healthy food advertising and unhealthy food advertising often use different advertising techniques [33] and also call for different advertising techniques in order to be effective [34].…”
Section: Sensory Advertising For Healthy Versus Unhealthy Foodmentioning
confidence: 99%
“…Participants were aware of a general definition of 'healthiness', when they articulated their considerations and perceptions on healthy family food provisioning. The use of nutritional slogans and catch phrases, indicated that health strategies employed by health researchers, governments and the food industry are being received by fathers (Adams & Geuens, 2007). They readily distinguished between 'healthy ' and 'unhealthy' or 'good' and 'bad' food. Home-made cooking and fresh ingredients were perceived to be healthy, whilst foods and ingredients such as sugar, salt, fat, processed items and 'junk food' were frequently referred to as 'bad'.…”
Section: Discussionmentioning
confidence: 99%
“…Personal characteristics and how these play a role in processing persuasive communication, such as the level of experience, risk perception, and health awareness, should be studied as well [40,41,42]. …”
Section: Discussionmentioning
confidence: 99%